Analyzing the Frequency of Emergency Room Visits and the Use of 119 Ambulance Services - Kang, Kyunghee (Fire Science and Engineering, 2020)
This study aimed to the socioeconomic and clinical characteristics associated with the use of 119 ambulance/private cars and the number of emergency room visits based on the 2017 data from the Korea Health Panel. The analysis revealed that during emergencies, the use of private cars (59.02%) was more common than 119 ambulance services (18.89%). Moreover, 119 ambulance users were significantly older, had a lower annual total household income, and had relatively more accidents than diseases when compared to private car users. On comparing the number of emergency room visits between single and multiple visits, there were statistically significant differences in age, total annual household income, season of use, and reasons for use for private car usage than 119 ambulances. The 119 ambulance service is an essential public safety net. Therefore, it is increasingly important to solve the frequent use of 119 ambulances by non-emergency patients, and efficiently utilize limited ambulance resources.